2020
DOI: 10.19105/al-lhkam.v15i1.2729
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Happiness and Religiosity for Pre-Prosperous Family: Study in Manado, Bandar Lampung, and Yogyakarta

Abstract: The results of this research (2017) want to explain the correlation between happiness and religiosity for poor families. The locus of this research is in the city of Manado, North Sulawesi Province, Bandar Lampung City, Lampung Province, and Yogyakarta City in Yogyakarta Special Region Province. This research is important because there is an assumption in the community that even poor people who are religious are certainly not happy. This assumption is further answered in this study, where there is a positive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…However, field evidence indicates select religious leaders continued hosting crowded services, implicitly endorsed by segments of Manado Muslims attending customary marriage and bereavement ceremonies with blatant pandemic dismissals. Previous studies found high religiosity among Manado adherents (Rajafi, Hamhij & Ladiki, 2020) and logical premises underlying Indonesian Ulema Council fatwas that elimated unfavorable perceptions against clerical entities (Sholeh, 2020). Nevertheless, the aforementioned public behaviors necessitated a re-evaluation of shifting societal attitudes towards scholars, particularly regarding compliance to directives on home worship.…”
Section: Introductionmentioning
confidence: 99%
“…However, field evidence indicates select religious leaders continued hosting crowded services, implicitly endorsed by segments of Manado Muslims attending customary marriage and bereavement ceremonies with blatant pandemic dismissals. Previous studies found high religiosity among Manado adherents (Rajafi, Hamhij & Ladiki, 2020) and logical premises underlying Indonesian Ulema Council fatwas that elimated unfavorable perceptions against clerical entities (Sholeh, 2020). Nevertheless, the aforementioned public behaviors necessitated a re-evaluation of shifting societal attitudes towards scholars, particularly regarding compliance to directives on home worship.…”
Section: Introductionmentioning
confidence: 99%